Implementation of The Jarimatika Method In Elementary School - Shevana Permata Sari, Meisya; Kaltsum, Talitha Nabilah; W, Wahyunengsih (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Jarimatika is a finger counting technique which makes the counting process more practical and fun for learners. This study aims to evaluate the effectiveness of this method in teaching mathematics on an upper-primary level, identify the barriers and facilitators to its implementation, and examine the perceptions of students and teachers concerning this pedagogical change. The study was carried out using a mixed-method approach, which included baseline and final testing alongside in-depth interviews and observations over several months. The findings demonstrated that Jarimatika was helpful in improving the students’ ability to count, motivating them to learn, and actively engaging them during the lessons. In addition, students’ confidence on the resolved math problems improved. However, the adaptation and training phases of teachers pose challenges which stem from lack of understanding of the method and minimal time to integrate it into lesson planning. More research is needed to determine the effects of the Jarimatika method on long-term academic outcomes, attitudes towards mathematics, and the sustained use of this technique in multiple educational contexts.